Relative roles of Arbuscular Mycorrhizae in establishing a correlation between soil properties, carbohydrate utilization and yield in Cicer arietinum L. under As stress - Neera Garg; Amandeep Cheema (Ecotoxicology and Environmental Safety, 2021)
Accumulation of As (metalloid) degrades soil by negatively affecting the activities of soil enzymes, which in turn reduce growth and yield of the inhabiting plant. Arbuscular mycorrhizal (AM) symbiosis can impart metalloid tolerance in plants by secreting glomalin-related soil protein (GRSP) which binds with As or inertly adsorb in the extraradical mycelial surface. However, profitable use of AM requires selection of the most efficient combination of host plant and fungal species. The current study, therefore designed to study the efficacy of 3 a.m. fungal species: Rhizoglomus intraradices (Ri), Funneliformis mosseae (Fm) and Claroideoglomus claroideum (Cc) in imparting arsenate As(V) and arsenite As(III) stress tolerance in Cicer arietinum (chickpea) genotypes (G) – relatively metalloid tolerant- HC 3 and sensitive- C 235. Roots were found to be more severly affected as compared to shoots which resulted into a major decline in uptake of nutrients, chlorophyll concentrations and yield with As(III) inducing more toxic effects than As(V). HC 3 established more effective mycorrhizal symbiosis and was able to extract higher nutrients from the soil than C 235. Ri was most beneficial in improving plant biomass, carbohydrate utilization and productivity followed by Fm and Cc which could be due to its capability to initiate highest percent colonization and least metalloid uptake in roots through higher glomalin production in the soil. Moreover, Ri was highly efficient in improving soil enzymes activities-phosphatases (PHAs), β-glucosidase (BGA) and invertase (INV), thereby, imparting metalloid tolerance in chickpea genotypes. The results suggested use of Ri-chickpea symbiosis as a promising strategy for ameliorating As stress in chickpea.